Medieval allegory and the building of the new Jerusalem - Meyer, Ann R. (Ann Raftery), 1963- (D.S. Brewer, 2003)
This book investigates the concept of the New Jerusalem, the City of God, as an architectural ideal during the middle ages, and the way in which it is represented allegorically in patristic writings, liturgy, building, and later literature. The author begins by examining its conceptual foundations in such sources as the Hebrew Bible, Bede's exegesis, the religious philosophy of Plotinus, and Augustine's theology.